The Development of executive function in early childhood - Zelazo, Philip David; Argitis, Gina. (Boston, Mass. : Blackwell Pub., 2003)
This monograph concerns the psychological processes underlying the development of executive function, or the conscious control of thought and action. It has long been clear that these processes change considerably in early childhood, transforming a relatively stimulus-driven toddler into a child capable of flexible, goal-directed problem solving. In a programmatic series of nine experiments, the authors examine circumstances that help or hinder executive function in 3- to 4-year-old children.
The development of executive function -- Study 1: memory and executive function -- Study 2: rule complexity and stimulus characteristics in executive function -- Study 3: what do children preseverate on when they perseverate? -- Study 4: negative priming and executive function -- The development of executive function: cognitive complexity and control, revised -- Appendix: summary of versions of the dimensional change card sort used -- Commentary: executive function in context: development, measurement, theory and experience / Stephanie M. Carlson.
Includes bibliographical references.
Keywords: Personality development; Developmental psychology; Child psychology